1999
DOI: 10.1002/etc.5620180906
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of Henry's law constants of thirteen polycyclic aromatic hydrocarbons between 4°C AND 31°C

Abstract: An understanding of the temperature dependence of the Henry's law constant for organic contaminants is critical when modeling the transport and fate of these contaminants in the environment. The Henry's law constants for 13 polycyclic aromatic hydrocarbons (PAHs) were experimentally determined between 4 and 31°C using a gas‐stripping apparatus. The Henry's law constants ranged between 0.02 ± 0.01 Pa m3/mol for chrysene at 4°C and 73.3 ± 20 Pa m3/mol for 2‐methylnaphthalene at 31°C. The temperature dependence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 44 publications
1
45
0
2
Order By: Relevance
“…A previous study suggested that colloidal hydrophobic organics could contribute about 12% of total water column hydrophobic organic mass to the truly dissolved concentration (Totten et al, 2001;Yan et al, 2008). The Henry's law constants (HLC) employed in this study were derived from the temperature-corrected values reported by Bamford et al (1999bBamford et al ( , 1999cBamford et al ( , 2002b. Salinity level is also important in studies on saline environments including coastal waters, estuaries, and harbors.…”
Section: Flux Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study suggested that colloidal hydrophobic organics could contribute about 12% of total water column hydrophobic organic mass to the truly dissolved concentration (Totten et al, 2001;Yan et al, 2008). The Henry's law constants (HLC) employed in this study were derived from the temperature-corrected values reported by Bamford et al (1999bBamford et al ( , 1999cBamford et al ( , 2002b. Salinity level is also important in studies on saline environments including coastal waters, estuaries, and harbors.…”
Section: Flux Calculationmentioning
confidence: 99%
“…The use of Tateya's DH w value leads to overestimate fluxes at low temperature and underestimate at high temperature compared with Tenhulscher's data. One decade ago, Bamford et al (1999b;1999c;2002b) measured H values and enthalpy (DH W ) for many PCB and PAH compounds and based on their experimental results it is possible to estimate H values for the remaining compounds. It is a significant improvement over previously published values because the database was developed relied on experimental datasets (Totten et al, 2003;Tsai et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The water depth was selected based on previous studies indicating that the equilibrium between gas and aqueousphases is achieved at less than 50 cm of water depth (Sahsuvar, Helm, Jantunen, & Bidleman, 2003;Harrison, Cape, & Heal, 2002;Jantunen & Bidleman, 2000;Bamford, Poster, & Baker, 1999;Bamford, Poster, & Baker, 2000;Betterton & Hoffman, 1988).…”
Section: Gas-stripping Experimentsmentioning
confidence: 99%
“…Our model approach and parameterisation build on a Langmuir-Hinshelwood reaction mechanism involving the decomposition of ozone and formation of longlived reactive oxygen intermediates (Shiraiwa et al, 2011;Berkemeier et al, 2016). Table S2 in the Supplement lists the parameterisations of the reaction rates.…”
Section: Heterogeneous Degradation Of Particulate Bapmentioning
confidence: 99%
“…Since direct K SA measurements are not available for PAHs, soot-air partitioning coefficients (K SA L kg −1 ) are estimated as the ratios of soot-water (K SW ; Jonker and Koelmans, 2002) and the air-water (K AW ) partitioning coefficients (dimensionless, temperature dependent; Bamford et al, 1999). Values of K SW vary substantially (up to a factor of 47 for the PAHs considered here) among relevant soot.…”
Section: Gas-particle Partitioningmentioning
confidence: 99%